ANDROID-BASED ENDLESS RUNNER GAME LEARNING MEDIA INNOVATIONS TO IMPROVE STUDENTS' MATHEMATICAL LITERACY - Leni Marlina; Aswandi Aswandi (Universitas Labuhanbatu, 2026)
Purpose –This study aims to evaluate the effectiveness of Android-based endless runner games as a learning medium for improving students' mathematical literacy through interactive gameplay that integrates mathematical problem-solving with entertainment elements.Methodology – This study employed a quasi-experimental pretest-posttest control-group design with 60 elementary students (grades 5-6), divided into an experimental (n=30) and a control (n=30) group. Data collection included a 20-item mathematical literacy test covering arithmetic, geometry, and measurement, plus feedback questionnaires measuring engagement and motivation—statistical analysis employed t-tests with normality and homogeneity of variance testing. Game quality was evaluated using the Game-based Learning Evaluation Framework.Findings – Results demonstrated significant improvements in mathematical literacy. The experimental group achieved substantially greater gains (30.8%) than the control group (6.1%), with statistical analysis confirming significance: t(58) = 5.67, p < .001, Cohen's d = 1.85, representing a considerable effect. Affective outcomes were equally positive: 90% of students reported increased confidence in mathematics, 85% expressed heightened interest, and overall engagement averaged 4.2/5.0, demonstrating the intervention's effectiveness in both cognitive and motivational dimensions.Contribution – This study contributes to validates situated learning and constructivist frameworks in mobile game contexts, demonstrating how seamless integration of learning content into gameplay mechanics enhances effectiveness. It offers educators an accessible, evidence-based mobile learning tool that simultaneously addresses achievement, engagement, and motivation—particularly valuable in resource-constrained educational settings